Profitability and Leverage Effect on Firm Value with Corporate Social Responsibility as Moderating Variable in Manufacturing Company - Rini Tri Hastuti; Janice Clairine Tertia (International Journal of Application on Economics and Business, 2023)
This research aims to determine the effect of profitability and leverage on firm value using corporate social responsibility as moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. A total of 168 samples selected from 56 companies during the research period using purposive sampling method. Research data obtained from secondary data, namely company’s annual report which are routinely published by companies listed on the Indonesia Stock Exchange every year. Also, Statistical Product and Service Solutions (SPSS) version 25 was used to process the data. The results showed that profitability and leverage had a significant positive effect on firm value. Corporate social responsibility as moderating variable has a significant effect on the relationship between profitability and firm value, but has no effect on the relationship between leverage and firm value.